Spelling Variations in A Dictionary of Setswana Personal Names - Otlogetswe, Thapelo J.; Ramaeba, Goabilwe (Lexikos, 2025)
This paper investigates spelling variation in A Dictionary of Setswana Personal Names (Otlogetswe and Ramaeba 2024), addressing a gap in existing research which has previously focused on general-purpose monolingual Setswana dictionaries (Otlogetswe 2015) but not specialized dictionaries such as the one on personal names. The study draws on orthographic guidelines outlined in the Standard Orthography of 1981 (Ministry of Education 1981) and Mokwalo o o Lolameng wa Setswana (Chebanne et al. 2008), while also tracing the historical development of Setswana orthography to early works by Lichtenstein (1928–1930; 1973) and Livingstone (1875). Using textual analysis, the paper critically examines dictionary headwords to identify and categorize spelling variants. The findings reveal numerous inconsistencies in the spelling of Setswana personal names, influenced by factors such as the coexistence of older and newer orthographic standards, dialectal variation across Setswana-speaking regions, and underlying morphological and phonological processes.Keywords: spelling variation, A Dictionary of Setswana Personal Names, Setswana, orthography